2001
DOI: 10.1074/jbc.m010446200
|View full text |Cite
|
Sign up to set email alerts
|

The Fission Yeast TOR Homolog,tor1 +, Is Required for the Response to Starvation and Other Stresses via a Conserved Serine

Abstract: Targets of rapamycin (TORs) are conserved phosphatidylinositol kinase-related kinases that are involved in the coordination between nutritional or mitogenic signals and cell growth. Here we report the initial characterization of two Schizosaccharomyces pombe TOR homologs, tor1 ؉ and tor2 ؉ . tor2 ؉ is an essential gene, whereas tor1؉ is required only under starvation and other stress conditions. Specifically, ⌬tor1 cells fail to enter stationary phase or undergo sexual development and are sensitive to cold, os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 42 publications
5
196
0
4
Order By: Relevance
“…TOR1 in S. cerevisiae is required for growth under high salt concentrations via regulation of GLN3 and GAT1 (Crespo et al, 2001). Likewise, fission yeast defective for Tor1 do not form colonies on medium containing high salt concentrations (Weisman and Choder, 2001). Hyperosmotic stress in mammalian cells causes cell shrinkage with a decline in water content, and rapid (o5 min) and reversible dephosphorylation of active S6K1 and 4EBP-1 independent of the stress-activated p38/c-Jun NH 2 -terminal kinase (JNK) MAPK pathways (Parrott and Templeton, 1999;Fumarola et al, 2005).…”
Section: Osmotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…TOR1 in S. cerevisiae is required for growth under high salt concentrations via regulation of GLN3 and GAT1 (Crespo et al, 2001). Likewise, fission yeast defective for Tor1 do not form colonies on medium containing high salt concentrations (Weisman and Choder, 2001). Hyperosmotic stress in mammalian cells causes cell shrinkage with a decline in water content, and rapid (o5 min) and reversible dephosphorylation of active S6K1 and 4EBP-1 independent of the stress-activated p38/c-Jun NH 2 -terminal kinase (JNK) MAPK pathways (Parrott and Templeton, 1999;Fumarola et al, 2005).…”
Section: Osmotic Stressmentioning
confidence: 99%
“…On the other hand, PKB1 has been reported to become activated within minutes upon heat shock, presumably reflecting the pro-survival effects of Akt/PKB (Konishi et al, 1997). S. pombe devoid of tor1p function are hypersensitive to cold stress, indicating that TOR might play a more general role in response to temperature (Weisman and Choder, 2001). …”
Section: Heat Shockmentioning
confidence: 99%
“…46,47 These results strongly suggest that TORC2 remains active in fission yeast cells starved of nitrogen, consistent with the observation that the activity of TORC2 and Gad8 is essential for the cell cycle arrest and sexual development after nitrogen starvation. [14][15][16]19,48 The TORC2-Gad8 pathway is responsive to glucose It has been reported that the mitotic control under low glucose conditions is altered in a strain carrying the tor1-L2045D mutation of the TORC2 catalytic subunit. 35 Therefore, we examined whether TORC2 activity is responsive to glucose, by shifting exponentially growing cells from the growth medium containing 3% glucose to the same medium lacking glucose.…”
Section: Torc2 Remains Active During Nitrogen Starvationmentioning
confidence: 99%
“…Among those is the fission yeast Schizosaccharomyces pombe, a genetically amenable eukaryote with nonessential TORC2, which eases mutational analysis of this particular TOR complex. [14][15][16][17][18][19][20][21] Fission yeast TORC2 is composed of the catalytic subunit Tor1 kinase and the regulatory subunits named Ste20, Sin1, Wat1 and Bit61. 17,19,22 The key downstream target of TORC2 in fission yeast is the AGCfamily kinase Gad8, as evidenced by the observation that the gad8 deletion mutant phenocopies the TORC2-defective mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the tsc genes result in a delayed response to nitrogen starvation as well as defects in amino acid uptake (21)(22)(23)(24)(25). The fission yeast genome encodes two TOR proteins, Tor1p and Tor2p (26,27). Although Tor2p, like Rhb1p, is essential for growth, tor1⌬ cells are sterile and unable to arrest in G 1 in response to nitrogen starvation (26,27).…”
mentioning
confidence: 99%